CLIMATE CHANGE AND LAND-BASED CONFLICT: THE IMPACT ON FOOD SECURITY IN NIGERIA - OGUIKE MIRIAM ADAEZE UJU (International Studies Journal)
Nigeria as a country is vulnerable to climate change issues. The adverse effect of climate change through drought, deforestation, flood, extreme weather condition, decline in soil texture, herders/farmers conflict, diseases and health issues, displacement, low human and physical capital, decrease in income, inequitable land distribution, poor infrastructure, etc, have caused poverty and food insecurity, etc. As a result of climate change, the number of land-based conflicts and deaths increased due to violence conflict within communities, groups, individuals and states. There is increase in flooding that leads to lack of access to transportation, food, health care, clean water, sanitation, economic activities. There is low and no income, violence, rape, drug abuse, crimes, kidnapping, displacement, abduction, banditry, environmental issues, among others. The aftermath of climate change is prominent on agricultural production such as livestock, crop, forest, fishery, nutrition, health and the general livelihood of the people. Land is one of the most valued gifts from God. The objective of the paper is to ascertain the connection between climate change and land-based conflict issues that lead to insufficient food supplies as experienced in Nigeria. The data were gotten from primary and secondary sources. The human needs theory of economic conflict was used to discuss the paper. This paper is divided into four sections. The first focuses on the introduction, conceptualization and theoretical framework. The second section expands on the issue of climate change and land-based conflict. The third examines the impact of climate change and land-based conflict on food security. The fourth section is the conclusion and the recommendations which include, effective policy, community adaptation structure, among others.